Educational Proposal for the Health of Patients with Diabetes Mellitus Type 2 - Rodríguez Campuzano, María de Lourdes; Rentería Rodríguez, Antonia; Rosales Arellano, Antonio; Rodríguez Soriano, Norma Yolanda (Pensando Psicología, 2014)
Health psychology focuses on the study of the psychological processes involved in health and illness, and incorporates a wide range of activities: health promotion, illness prevention, and attention for both the sick and for people suffering the aftereffects of illness. It also plays a role in the provision of health services according to the needs of the recipients. Given the worldwide prevalence of diabetes mellitus type 2, the conditions and quality of life of people with this disease has become a public health issue that must be addressed seriously. Although the treatment of diabetes is the direct responsibility of professionals and institutions working in this area, a multidisciplinary effort would help greatly in finding a solution or improving the condition, and psychology, as a generator of knowledge that could be applied, therefore has a place in this wider working team. The objective of this research study was to design an educational proposal based on the psychological model of biological health (Ribes, 1990) to promote preventative behavior in patients with diabetes mellitus type 2.
Keywords: diabetes mellitus type 2; psychological model of biological health; educational proposal